An Inertial Algorithm of Generalized f -Projection for Maximal Monotone Operators and Generalized Mixed Equilibrium Problems in Banach Spaces - Lawal Umar; Tafida M. Kabir; Ibrahim U. Haruna (African Scientific Reports)
In this paper, we study a modified hybrid inertial algorithm of generalized f-projection for approximating maximal monotone operators and solutions of generalized mixed equilibrium problems in Banach spaces. Our results generalize and improve many recent announced results in the literature.